In situ polymerization synthesis and characterization of single wall nanotubes/poly(vinyl)triazole nanocomposites - Beyaz, Saadet K.; Tekin, Nalan; Kara, Ali; Simsek, Eyup; Cakmak, Gulbeden; Guney, H. Yuksel; Lamari, Farida D. (Sage Publications Ltd, 2011)
The synthesis of single wall nanotubes (SWNT)/poly(vinyl)triazole (PVTri) composites by in situ emulsion polymerization method and its chemical and physical properties were investigated throughout this work. The surface modification of the SWNT by nitric acid treatment and air oxidation has improved the dispersion of the SWNT in the PVTri matrix. The SWNT/PVTri composite is obtained by covalent bonding of the carboxyl terminated SWNTs to PVTri. The effect of covalent bond formation between PVTri and SWNT on the thermal and electrical properties of the composite is also studied. The spectroscopic, thermal, and microscopic analysis has confirmed the structure, homogeneity, and the morphology of surface functionalized SWNT and SWNT/PVTri composites. SWNT/PVTri composites showed enhanced chemical stability in many common solvents and high electrical conductivity.
Keywords: poly(vinyl)triazole; carbon nanotubes; in situ polymerization; nanocomposites; thermal properties; electrical properties